Notes philologiques sur la légende ougaritique de Danel et d'Aqhat. I - Caquot, André
ersch. 1988; 1. mt rpi. 2. uzr. 3. lcpr ?mr a?rh. 4. dcšy lnh. 5. ncmy. 6. ?kpt il klh. 7. ygr. 8. kbcl.ky?wy.ycšr